Establishment of CSUASOi001-A, a non-integrated induced pluripotent stem cell line from urine-derived cells of a Chinese patient carrying RS1 gene mutation - Xin Yan; Yonglong Guo; Juan Chen; Zekai Cui; Jianing Gu; Yini Wang; Shengru Mao; Chengcheng Ding; Jiansu Chen; Shibo Tang (Stem Cell Research, 2019)
X-linked juvenile retinoschisis (XLRS) is one of the most severely affected genetic causes of irreversible retinal degeneration diseases in young males, especially school-age boys. Here, we generated induced pluripotent stem cells (iPSCs) from a Chinese 11-year-old male with clinically diagnosed XLRS. Urine sample was collected with appropriate cooperation, then isolated cells were expanded for subsequent reprogramming procedure using integration-free Sendai virus. The newly derived CSUASOi001-A iPS cell line harboring the c.304C > T mutation in the RS1 gene (p.R102W) provides a useful resource to investigate pathogenic mechanisms in XLRS.